SURGICAL TREATMENT OF CAROTID BODY TUMORS — A SINGLE CENTER EXPERIENCE AND LITERATURE REVIEW - Catarino, Joana (2019)
Introduction: Carotid body tumors (CBT) are rare (1–2/100.000) slow-growing, hipervascular neuroendocrine tumors, originate from the neural crest. Their exact cause is unknown. Most are sporadic, but a subset (25%) are associated with hereditary paraganglioma syndrome. Complete surgical removal is the treatment of choice for all CBTs. Methods: This is a retrospective study of patients with CBT, who were treated at our institution between 2012 and 2018 and a literature review. Results: Over the last 6 years, 13 patients were treated for CBTs in our center (7 female, 6 male), who were aged 46 years (range 14–72 years). Three (23%) of the tumors were Shamblin I, eight (61,5%) Shamblin II and two (15,5%) Shamblin III. The median tumor diameter was 3,6 cm (range from 2,5 to 6,6cm). We performed preoperative embolization with micro coils in 5 patients (39%), 2 days before surgery.Two patients (40%) presented with Shamblin's III tumors (one with cranial extension) and 3 (60%) had tumor >5cm, Shamblin II. There were no postembolization strokes, TIAs or access site hematomas. All 13 CBTs tumors (including large tumors, extended cranially and Shamblin's III) were treated with resection alone (100%), without need for arterial resection or reconstruction. Average blood loss was 130 mL (range from 100 to 180 mL). In this study the overall rate of complications was 7% (1 patient) who had permanent hoarseness due to vagus nerve resection (vagus sacrificed due to tumor involvement), there were no cases of stroke, TIA or hematoma . There were no mortalities in the perioperative period or during follow-up. Conclusion: CBTs are rare and surgical excision can be very demanding and laborious. From our experience, pre-operative embolization is safe and may be of value in large and Shamblin III tumors.